Neuroprotective metabolites from the endophytic fungus Penicillium citrinum of the mangrove Bruguiera gymnorrhiza. (June 2015) - Wu, Yan-Zhi; Qiao, Fang; Xu, Guo-Wei; Zhao, Jie; Teng, Jun-Fang; Li, Chun; Deng, Wen-Jing
Graphical abstract: Two new compounds, ( Z )-7, 4′-dimethoxy-6-hydroxy-aurone-4-O- β -glucopyranoside (1 ), and (1 S, 3 R, 4 S )-1-(4′-hydroxyl-phenyl)-3, 4-dihydro-3, 4, 5-trimethyl-1H-2-benzopyran-6, 8-diol (2 ), were isolated from the endophytic fungus Penicillium citrinum of Bruguiera gymnorrhiza . Compound 1 exhibited potent neuroprotective activity in MPP + -induced oxidative damage in PC12 cells. Highlights: A marine-derived fungus Penicillium citrinum was isolated and investigated. Two new metabolites were identified in the endophytic fungus. Compound 1, an aurone glycoside, exhibited potent neuroprotective activity. Abstract: Two new compounds, named as ( Z )-7, 4′-dimethoxy-6-hydroxy-aurone-4- O - β -glucopyranoside (1 ), and (1 S, 3 R, 4 S )-1-(4′-hydroxyl-phenyl)-3, 4-dihydro-3, 4, 5-trimethyl-1H-2-benzopyran-6, 8-diol (2 ), were isolated from the endophytic fungus Penicillium citrinum of Bruguiera gymnorrhiza . Their structures were elucidated on the basis of spectroscopic analysis. Additionally, compound 1 exhibited potent neuroprotective activity in 1-methyl-4-phenylpyridinium-induced oxidative damage in PC12 cells.